The impact of cost-benefit analysis on decision making concerning the development of the urban transport system: case of Kaunas City - Dumbliauskas, Vytautas; Grigonis, Vytautas; Barauskas, Andrius (Transport, 2018)
The formulation of scenarios for developing the urban transport infrastructure requires decisions mainly based on the intuition of experts in transport and highly influenced by public interest groups, business entities and political opinions. However, the reached decisions sometimes fail to be the most efficient. Therefore, to avoid errors and ensure the development of a sustainable transport system, the economical appraisal of infrastructure development scenarios is necessary. The economic evaluation of the developed scenarios can be carried out through macro-simulation and cost-benefit analysis. This paper deals with the Kaunas City Master Plan providing solutions to transport infrastructure development. According to the Master Plan, solutions can be classified considering 3 cathegories (priorities), although the detailed sequence of implementation is not given. With the help of macro-simulation, this study arranged Master Plan solutions into scenarios, checked all 20 scenarious and established an implementation order based on the theory of cost benefit analysis. The identified order substantially differs from the priorities set in the Master Plan.